Radiotherapy for a rare phosphaturic mesenchymal tumor in the middle ear presenting with oncogenic osteomalacia: A case report. Issue 38 (24th September 2021) - Takaoka, Taiki; Tomita, Natsuo; Shido, Yoji; Baba, Satoshi; Fukushima, Mayu; Sugie, Chikao; Shibamoto, Yuta
Abstract: Rationale: Phosphaturic mesenchymal tumor (PMT) is a rare neoplasm causing oncogenic osteomalacia. Surgery remains the definitive treatment for PMT, and radiotherapy is seldom employed. However, surgery for PMT involving the head and neck is often difficult due to the local invasion and complicated anatomy. We report the first case of PMT, which was successfully treated with the combination of radiotherapy and supplementation of activated vitamin D. Patient concerns: A 55-year-old woman suffered from pain in the hip and bilateral femur. Serum phosphate and calcium decreased to abnormal levels. Serum alkaline phosphatase and fibroblast growth factor 23 increased to abnormal levels. The hearing loss of the right ear had continued and a middle ear tumor was revealed. Diagnoses: Subsequent biopsy provided the diagnosis of PMT that caused oncogenic osteomalacia. These clinical and pathological characteristics were consistent with and provided the final diagnosis of benign PMT. Interventions: Surgery of the PMT was difficult and the patient underwent radiotherapy. The prescribed dose was 36 Gy in 10 fractions. Simultaneously, the patient started supplementation of 1, 25-dihydroxyvitamin D3 (1–2 μg/day) and continued for 2 years. Outcomes: Near-complete resolution of the symptoms was achieved and abnormal laboratory values recovered. At 5 years of follow-up, the irradiated tumor showed no regrowth. Severe hearing loss of the right ear was not observed. Lessons: Radiotherapy was effective for the PMT and could be an important treatment option for inoperable cases.